Generasi Hamba Google: Saya Klik maka Saya Pintar - Maria Florentina Rumba; Yosafat Yulianus (Media: Jurnal Filsafat dan Teologi, 2023)
This paper aims to offer a critical discussion regarding the advancement of digital technology. The author directs attention to the so-called generation z who have lost control of using digital technology. The critical ideas offered aim to educate the younger generation, who live in a 'click' mentality and have become Google's slaves. This critical discussion also aims to build a critical and responsible intellectual attitude in the digital era. The author designed this research as a literature review. Amid the rapid advancement of digital technology, generation z must remain critical and not become a Google slave. Flexibility and adaptability in a changing world must be accompanied by an attitude of responsibility. They must have the ability to give value to their activities in digital technology. Technological literacy must be balanced with self-discovery. Literacy culture is a solution to achieve a critical awareness and an attitude of responsibility in dealing with advanced digital technology.